78.7k views
1 vote
Which expression is equivalent to the expression below?

StartFraction m + 3 Over m squared minus 16 EndFraction divided by StartFraction m squared minus 9 Over m + 4 EndFraction

User Mibou
by
3.7k points

2 Answers

2 votes

Explanation:


\frac{m + 3}{ {m}^(2) - 16} / \frac{ {m}^(2) - 9 }{m + 4} \\ \\ = \frac{m + 3}{ {m}^(2) - {4}^(2) } / \frac{ {m}^(2) - {3}^(2) }{m + 4} \\ \\ = \frac{m + 3}{ ({m} + 4)(m - {4})} / \frac{ ({m} + 3)(m- {3}) }{m + 4} \\ \\ = \frac{m + 3}{ ({m} + 4)(m - {4})} * \frac{ m + 4 }{({m} + 3)(m- {3})} \\ \\ = \frac{1}{ (m - {4})} * \frac{ 1}{(m- {3})} \\ \\ = \frac{1 * 1}{ (m - {4}) * (m- {3})} \\ \\ = (1)/( m^(2) + ( - 4 - 3)m + ( - 4)( - 3)) \\ \\ = (1)/( m^(2) + ( - 7)m + 12) \\ \\ = (1)/( m^(2) - 7m + 12)

User Dergyll
by
4.5k points
4 votes

Answer:

It's actually B -
(1)/((m-4)(m-3))

Explanation:

Edg2020

User Fireburn
by
4.5k points